Drink : the intimate relationship between women and alcohol - Johnston, Ann Dowsett (New York, NY : HarperWave, 2013)
"In Drink: The Intimate Relationship Between Women and Alcohol, award-winning journalist Anne Dowsett Johnston combines in-depth research with her own personal story of recovery, and delivers a groundbreaking examination of a shocking yet little recognized epidemic threatening society today: the precipitous rise in risky drinking among women and girls. With the feminist revolution, women have closed the gender gap in their professional and educational lives. They have also achieved equality with men in more troubling areas as well. In the U.S. alone, the rates of alcohol abuse among women have skyrocketed in the past decade. DUIs, "drunkorexia" (choosing to limit eating to consume greater quantities of alcohol), and health problems connected to drinking are all rising--a problem exacerbated by the alcohol industry itself. Battling for women's dollars and leisure time, corporations have developed marketing strategies and products targeted exclusively to women. Equally alarming is a recent CDC report showing a sharp rise in binge drinking, putting women and girls at further risk. As she brilliantly weaves in-depth research, interviews with leading researchers, and the moving story of her own struggle with alcohol abuse, Johnston illuminates this startling epidemic, dissecting the psychological, social, and industry factors that have contributed to its rise, and exploring its long-lasting impact on our society and individual lives"--
"An exploration of the rise in alcohol consumption and abuse among women in recent years. Drink covers health risks, marketing, current trends and sociological underpinnings of this new epidemic. The author beautifully weaves reportage with her personal recovery story into a compelling and informative narrative addressing one of the most pressing issues for women today"--
Singing Backwards. The monkey diary: the beginning of the end ; Out of Africa: a family unravels ; You've come the wrong way, baby: closing the gender gap on risky drinking ; The future is pink : the alcohol industry takes aim at the female consumer ; The age of vulnerability: the consequences of drinking young ; Binge: the campus drinking culture. -- On the Edge of the Big Lonely. Searching for the off button: drinking to forget, drinking to numb ; Self-medication: mood disorders and alcohol, a seductive combination ; Romancing the glass: a slim stem of liquid swagger ; The modern woman's steroid: popping the cork on mother's little helper ; The last taboo : drinking and pregnancy ; The daughters' stories : growing up with an alcoholic mother. -- Healing. In which everything changes: getting sober, staying sober ; Breaking the trauma cycle: the mother-and-child reunion ; Something in the water: shaping a strong public health strategy ; Wrestling with the God thing: spirituality and sobriety ; Stigma: a call to action ; Becoming whole: in which I recover my self.
Includes bibliographical references (pages 289-304).
Keywords: Women -- Alcohol use; Women alcoholics; Women alcoholics -- Rehabilitation